Analisis Perlindungan Hukum Bagi Pihak-Pihak Yang Memiliki Hak Atas Tanah - Alya Yaseera; Shifra Kamalia (Hakim, 2023)
If viewed etymologically Yoeti (1996) the term tourism itself comes from Sanskrit which has the same meaning as tour, which means going around from one place to another. Karyono, (1997) Tourism is a series of activities carried out by humans both individually and in groups in the territory of other countries. These activities use facilities, services and other supporting factors provided by the government and/or the community, in order to realize the wishes of tourists. According to Mappi (2001) Tourism is a travel activity or part of these activities which is carried out voluntarily and temporarily to enjoy tourist objects and attractions.